Analisis Perhitungan Pajak Penghasilan Badan Pada PT. Garuda Mas Perkasa - Togatorop, Erika Tamani; Lubis, Citra Windy (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2025)
This study aims to analyze the calculation of Corporate Income Tax (PPh Badan) at PT. Garuda Mas Perkasa, particularly during the delay in tax payment in 2020. The main focus of the research includes the method of calculating corporate income tax during the delay, the obstacles that led to the late payment, and the efforts made by the company to address sudden changes in tax regulations. This research uses a qualitative descriptive approach, with data collected through company financial documentation and interviews with relevant parties. The results show that the delay in paying corporate income tax was influenced by the company's financial condition due to the impact of the COVID-19 pandemic, as well as a lack of preparedness in facing regulatory changes. PT. Garuda Mas Perkasa implemented several adjustment strategies, such as improving the internal reporting system and conducting regular consultations with tax consultants, in order to minimize the risk of penalties and tax sanctions in the future.